Cyberspace and women’s human rights in the international legal order: Transnational risks and gender-based violence - Estrada Tanck, Dorothy (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Cyberspace has exacerbated certain transnational risks, such as cyber-discrimination, harassment, and aggression, particularly affecting women and girls on the basis of gender. Gender-based violence as a form of gender discrimination, including in its new forms, harms women and girls disproportionately, especially in their rights to equality, freedom from violence and freedom of expression. This article explores the contributions offered by different sources of law, in particular international human rights law, to address these gender-based risks and to prevent, eradicate and redress discrimination and gendered cyber-violations. It also analyses the opportunities that both the technological advancement concerning cyberspace, and the normative and interpretative standards developed to this effect, present for the construction of gender equality for women and girls worldwide.
Keywords: cyberspace; gender-based violence; human rights of women and girls; cyber-violations; gender equality